Effect of Water-Cement Ratio on Mix Design and Mechanical Strength of Copper Slag Aggregate Concrete. Issue 1 (September 2020) - Panda, Swetapadma; Sarkar, Pradip; Davis, Robin
Abstract: In concrete, the distinct influence on most or the entirety of the properties is the measure of water utilised in the matrix. In concrete mix design, the water-cement ratio is responsible for binding all constituents of concrete together. If the water-cement proportion is higher, it brings about wider spacing between the cement aggregates and thus, influences the compaction. Correspondingly, concrete's durability and compressive strength are decreased due to increased dampness levels. Especially with added fine aggregates the water demand increases because of the increased surface area of concrete which prompts a higher water-cement ratio. Wider spaces are formed between the aggregate materials with the addition of extra water and when the moisture vaporises, voids are filled up with air. The subsequent insufficient compaction lessens the concrete's strength. Sets of basic experimental investigations were conducted to examine the impact of various water-cement proportion on mix design and mechanical strength of concrete incorporated with fine aggregate in terms of copper slag. Natural sand replaced with copper slag with four different percentage and correlation coefficients between mechanical properties of copper slag concrete were also evaluated.